The gastrointestinal breach: understanding enterocutaneous fistula - Joshi, Rajeev M.; Soni, Gagan; Khalife, Asma; Ranvir, Deepak; Telang, Bhushan (International Surgery Journal, 2023)
The term "fistula" usually refers to abnormal communication between two epithelial surfaces and an enterocutaneous fistula (ECF) is an abnormal communication between any part of gastrointestinal (GI) tract and skin and lined by epithelium or granulation tissue. Common causes include trauma during abdominal surgery, inflammatory bowel disease, malignancy, infection, radiation etc. Sepsis and malnutrition are the leading causes of mortality. In cases of high-output fistula, it is essential to adequately replace the excessive fistula discharge. The patient's nutrition plays a crucial role in the successful management of ECFs. If the patient can tolerate oral or enteral feeding, it should be initiated promptly. However, if oral intake is not feasible, parenteral nutrition should be considered. Adequate wound care, including diligent skincare and timely drainage of localized abscesses, is necessary. Before conducting definitive investigations and initiating treatment, it is important to ensure proper resuscitation and stabilization of the patients. Surgical intervention should be approached in staged manner and should not be rushed to prevent failure in managing this complex condition. To conclude management of ECF is complicated and needs multidisciplinary approach. Initial focus for remedy is on treating fluid and electrolyte disturbances, comprehensive treatment of sepsis, management of fistula output, skin care and psychological support.